The Role of the District Head in Improving the Performance of Civil Servants at the Office of the District Head of Galang - Kusmanadi, Kusmanadi (Borong Newinera Publisher, 2025)
This study aims to analyze the role of sub-district heads in improving the performance of Civil Servants (PNS) at the Galang Sub-district Office, Deli Serdang Regency, and to identify inhibiting factors in the implementation of these roles. This study uses a qualitative approach with observation, interview, and documentation study methods. The results of the study indicate that the role of sub-district heads is divided into three categories based on Mintzberg's theory, namely interpersonal roles, informational roles, and decision-making roles. Active, participatory, and passive approaches are used synergistically in implementing these roles. The inhibiting factors found include limited human resources, minimal budget, unproductive work culture, and ineffective communication and supervision systems. This study concludes that the role of sub-district heads is very important in building an efficient and professional work environment through an adaptive and communicative leadership approach.